STEADY-STATE ANALYSIS ON COOLANT SYSTEM OPERATING OF THE TRIGA2000 USING FUEL PLATE TYPE - sukmanto sukmanto dibyo (Direktorat Pengelolaan Fasilitas Ketenaganukliran (DPFK) RSG-GAS, 2021)
The TRIGA2000 is one of the nuclear research reactors in Indonesia. TRIGA reactor fuel element is rod type, studies of the TRIGA reactor using plate type fuel have been carried out. One primary coolant pump is required to overcome the safety factor on the core which uses plate-type fuel. Besides that, changes in the reactor core configuration have an effect on the ability to transfer heat from the core to the coolant. Therefore, it is necessary to analyze the operating parameters of the cooling system including temperature, pressure and flow rate. This operating data is important, which is required by the operator to estimate the reactor coolant condition. The purpose of this paper is to analyze the cooling system parameters under normal steady-state operation where the primary coolant capacity is 50 kg/s and the reactor power is determined to be 1 MW. Calculation of cooling system at normal condition is carried out using the ChemCAD.6.1.4 computer program. This is also required in providing the reactor's Safety Analysis Report (SAR) document. The results show that the TRIGA reactor which uses plate-type fuel elements can be operated safely. However, in case of coolant temperature to the reactor core exceeding the design data (35oC), it is necessary to be considered against the operational reliability of the cooling system